Experimental and numerical evaluation of different vortex generators on heat transfer. (5th September 2016) - Hosseini, M.; Ganji, D.D.; Delavar, M. Aghajani
Highlights: Rectangular and triangular decorated bars on cooling of a hot bar were studied. Experimental and numerical methods have been applied. Heat transfer of rectangular arrange of bars was more compared to other modes. Abstract: Effect of Sinusoidal (Sin), Wave and Broken obstacles followed by rectangular and triangular decorated bars on cooling of a hot bar was investigated experimentally and numerically in the present investigation. Experiments were performed in a wind tunnel in which transient heat transfer were considered on the hot bar. The obtained results revealed that the heat transfer corresponding to the Sin obstacles followed by rectangular arrange of bars was more compared to other modes.